Extramural English as a new reality in ELT: A PRISMA systematic review - Maristy, Humaera Silvia (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2023)
The purpose of this study is to review the trends and key conclusions of research on Extramural English activities in English language teaching (ELT) approaches. Several databases, including Scopus, Taylor & Francis, and Google Scholar, were examined and 8 articles in all were examined for this purpose. The research methodology employed was a PRISMA systematic review. A content analysis technique was used to assess the articles. The study's findings showed that extramural English in ELT became more popular among researchers in Sweden after 2012. This research sought to look at the trends and conclusions made by the publications. Secondary school students served as the primary participants in the articles that were chosen. It suggests that more research on additional potential participants from different levels is necessary. This study recommends using a qualitative research design in future studies to learn more about students' extramural English activities, which may shed new light due to a different methodological approach. It was discovered that there aren't many studies that focus on the new reality of digital Extramural English practice. Because there is still much room for research in this area, future researchers are encouraged to talk more about Extramural English in relation to technology.